Evaluation of the use of Cratylia argentea as a supplement in diets for broilers (Revista Sistemas de Producción Agroecológicos, 2013)
Forage legumes can consider to replace part of the protein required in poultry diets in order to reduce costs in family economy. The purpose of this research was to determine the advantages of Cratylia argentea include it in different levels, in diets for broiler feed. This work was carried out with 36 broilers (Arbor acres) 15 days of old with an average weight of 450 ± 20 g, they received balanced diets: the same protein (21%) and caloric content (2,900 kcal ME (metabolizable energy) / kg), to which different levels are included Cratylia argentea flour (HC) as follows: Control T0 = 0%, T1 = 5%, T2 = 10%, and T3 = 15%. The main ingredients used were flour beef, soybean meal, rice flour and corn. For five days there was a habituation of birds to these diets that were offered, every five days the birds were weighed to determine their weight gain. To measure the biological value (BV) protein, excreta were collected for three days which were analyzed in the Laboratory of Animal Nutrition; the same process was carried out with diets offered and HC. The statistical design used was completely randomized design, four treatments, three replicates and three experimental units. Chickens were better total weight gain (P
Keywords: forage legume; feeding; broilers